The Role of Nutrition in Increasing Milk Productivity of Breeding and Breeding Cows - Xujamov Jurabek Nayimovich; Avalbekova Sabrina Obidjon qizi (American Journal of Biomedicine and Pharmacy, 2025)
This article examines the feeding, care, use, and productivity of cows in order to fully realize their genetic potential, and the nutrition factor is a factor that determines the vital activity of animals. The level of productivity of animals, the quality of reproduction, their health and the quality of their breeding and breeding are directly related to the level of feeding and the quality of the feed. The origin and productivity of the cows in the experimental groups were determined using the primary zootechnical documentation available on the farm. The feeding and care conditions of the cows in all experimental groups were the same. The milk yield of the cows was monitored every 10 days using the AFIMILK milking machine, the fat content of the milk was determined once a month by the Gerber method, and the protein was determined by the Keldal method once a month.